Morin's Complex Thinking and Besse's Landscape as strategies for a new vision on the planning of green areas and multifunctional urban ecological corridors - Graviola, Gabriela Rosa; Pena, João Carlos; Ribeiro, Milton Cezar; Constantino, Norma Regina Truppel (National Journal of City Management, 2021)
The Cartesian world view established a model of development for western cities that led to a number of environmental, social, and economic consequences. In order to overcome these challenges, a reform in current thinking is necessary. Thus, this article aims to intertwine the concepts of complexity of Edgard Morin and the concepts of landscape proposed by Jean Marc-Besse in order to better understand how the interaction of these two authors can help guide city planning with a focus on sustainability. As a case study, we used the municipality of Rio Claro-SP. The method used was a comparative study of the main works by the authors, as well as an analysis of the process of planning ecological corridors in the chosen municipality, following the steps proposed by Besse. As a result, it was observed that the interaction between landscape and complex thinking is fundamental for creating a far-reaching knowledge network. In the search for sustainability, the dialogic method can be an important tool for creating strategies to solve contemporary challenges of urban planning.